(untitled) (European Journal of Marketing and Economics, 2024)
We review the Supply Chain (SC) planning in Defence operations. Our main focus is an exploration of the literature to identify the significant factors concerning SC planning and the way they affect the implementation of Decision Making Processes (DMP) in (primarily) military operations. We take as our starting point the logistics of Alexander the Great’s army, to identify the key factors that led to his legendary success and to understand how these factors influenced his strategic decisions. We then review the practices, and evaluate the effectiveness, of countries and international bodies that have already implemented such SC management and planning systems to assist in their defence activities’ decisions. Then, we illustrate the literature review with specific modern day examples of military deployment. Although many countries have invested in IT systems which may provide up to date information and cost-effectiveness suggestions, nevertheless, the utility of these systems in the defence sector, seems to be often surrounded by emotions and private or vested interests. Our research thus far suggests that there are substantial benefits to be gained by adopting a relevant decision framework to be implemented among military activities. At the end we attempt an identification of the key factors concerning SC planning since Alexander’s time and their effectiveness level in recent defence operations among other existing DMP tools.